Hazard Identification and Occupational Risk Mapping in Asphalt Paving Work on the Main Access Road to the Rongi Micro Hydro Power Plant, Sampolawa District - La Sianto; Sonya Zahir (Journal of Innovative and Creativity, 2026)
The study purpose was to identify occupational hazards, assess risk levels, and formulate appropriate risk control measures in asphalt paving activities on the main access road to the Rongi Micro Hydro Power Plant (PLTMH), Sampolawa District. Asphalt paving work involves high-risk construction activities due to the use of heavy equipment, exposure to hot asphalt materials, interaction with traffic, and environmental conditions such as sloped terrain and high rainfall. These conditions require systematic Occupational Health and Safety (OHS) management to prevent work accidents and improve safety performance. Materials and methods: This study employed a qualitative descriptive approach using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. Data were collected through field observations, interviews with workers and supervisors, documentation, and literature review. Risk levels were determined using a semi-quantitative risk matrix by assigning numerical values to likelihood and severity, and calculating the risk score to classify hazards into risk categories. Results: The study identified 50 potential hazards across eight stages of asphalt paving activities, consisting of 16 high-risk hazards and 34 medium-risk hazards. High-risk hazards were mainly associated with heavy equipment operation, hot asphalt exposure, chemical substances, traffic interaction, and worker fatigue. Environmental factors also contributed significantly to the occurrence of occupational hazards. These findings indicate that asphalt paving activities require strict safety management and priority control measures. Conclusions: Asphalt paving work on the PLTMH Rongi access road presents significant occupational safety risks that must be managed through systematic hazard identification, risk assessment, and risk control. The implementation of engineering controls, administrative measures, and proper use of personal protective equipment is essential to reduce accident potential and improve construction safety performance.